Ireland and the Paris Olympic Games (1924): a difficult journey successfully negotiated. Issue 3 (3rd July 2019) - Hunt, Tom
ABSTRACT: Ireland first competed as an independent nation in the Olympic Games at Paris in 1924. The Irish presence in Paris was largely due to the work of J.J. Keane, who became the first Irish member of the International Olympic Committee (IOC) in 1922. This made it possible for Ireland to compete independently in the Olympics. As Keane lobbied for IOC membership, he also persuaded the two rival athletic controlling bodies of Irish athletics to abandon their claims and merge into a single controlling body for the sport. An Irish Olympic Council was established by Keane to manage the Irish entry for the Paris Games. Olympic recognition was achieved against a background of tumultuous political events in Ireland that included a war of independence, a civil war and partition of the island. The British Olympic Association consistently opposed demands for independent Irish Olympic representation and in 1924 attempted to limit Irish Olympic jurisdiction to the territory of the Irish Free State, an attempt that was firmly rejected and resisted by Keane on behalf of the Irish Olympic Council. This was complicated by Irish participation in the Olympic football competition.